PENGARUH INKLUSI KEUANGAN PADA ERA DIGITAL ECONOMI TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Febriaty, Hastina; Rahayu, Sri Endang; Nasution, Eri Yanti (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
This study aims to determine the effect of financial inclusion in the digital economy era on Indonesia's economic growth and to produce financial inclusion strategies and policies in addressing income inequality in Indonesia. This goal is based on the existence of high financial inclusion and high economic growth that has not been able to overcome income inequality that occurs in people in Indonesia. This type of research is the descriptive statistical method. The types and sources of data used are secondary data obtained from the  Central Bureau of Statistics, Bank Indonesia, books, journals and other sources. The results of this study indicate that partially the effect of financial inclusion such as the number of credit accounts, the number of savings accounts (DPK) and the number of MSME loans has no significant effect on economic growth while the number of ATM machines has a significant effect on economic growth and the amount of JTAB savings has a positive and significant effect on economic growth. economic growth while simultaneously (together) the JATM, JKB, JRK, JTAB and UMKM variables affect economic growth in Indonesia